Relationship between Indian Ocean dipole mode and summer monsoon - BALA , INDU; SINGH , O. P. (MAUSAM, 2008)
Utilizing the Indian Ocean Dipole Mode (IODM) and Indian Summer Monsoon Rainfall (ISMR) data for the period 1960-2002 the relationships between the IODM and monsoon onset over Kerala and rainfall distribution over the country have been studied. It has been found that stronger/weaker western pole during April-May is associated with delayed/early monsoon onset over Kerala. Stronger eastern pole during March-April seems to be associated with enhanced seasonal (June-September) rainfall over peninsular India. The IODM index of July-August can provide good indications of summer monsoon activity over peninsular India during the withdrawal phase of the monsoon, i.e., during September.